Micro-explosion phenomenon of tri-fuel emulsion - Muhammad Mukhtar, Noor Awalludin (2020)
Compression Ignition engine has a significant share in transportation and many major industries because of the ability to withstand high compression ratio, reliable and cost effective. While effort is there to generate micro-explosion for the simultaneous reduction of particulate matter and NOx, the phenomenon has not been investigated in the high pressure spray injection and engine light atmosphere. In this study, tri-fuel emulsions consist of diesel, ethanol and biodiesel which is believed to be capable of secondary atomization advantage known as micro-explosion phenomenon were prepared using an ultrasonic emulsifier. The two-level factorial design method was employed with Design of Experiment platform to analyze the effect of ultrasonic emulsification control factors and the formulation ratio of ethanol and biodiesel into tri-fuel emulsion on the obtained physicochemical properties. Physicochemical properties include density, viscosity, surface tension and average droplet size. Evidence that micro-explosion had occurred on a spray droplet injected from the high-pressure common rail fuel injection system was identified using shadowgraph technique with the aid of high-speed camera under high temperature in the optical constant volume combustion chamber. The single-cylinder engine was set up to attain tri-fuel emulsions combustion characteristics. Ignition delay, heat release rate, and in-cylinder pressure were obtained and analyzed. From the fuel characterization study, the result revealed that density was influenced significantly by the ethanol content (single interaction) with the P-Value of 0.0023. Meanwhile, the viscosity level was influenced strongly (with the P-value < 0.0001) by the ethanol interaction with biodiesel ratio. Cycle setting plays a significant role to balance that interaction. Moreover, surface tension level was significantly dependent on cycle setting and ethanol content with P-value 0.0383. Surface tension decrease as ethanol level was increased. However, high cycle setting reduces the slope stiffness representing the decrease of the surface tension. Meanwhile, amplitude plays a significant role in manipulating biodiesel effect on the increase or decrease of the surface tension. Average droplet size also was triggered by amplitude setting prompt to biodiesel percentage in Tri-fuel emulsion. When high biodiesel fraction was combined with low amplitude setting, the average droplet size increased dramatically by 80%. Low amplitude setting while reducing the cycle setting causes the size to increase dramatically by 372%. Low-intensity micro-explosion phenomenon known as puffing occurred on a single droplet from a fuel injection spray. Puffing was regarded as single and double side puffing. The impact on droplet was appreciated via centricity, diameter, spread axial distance and surface area plot. The impact of micro-explosion phenomenon on single droplet opens up the door in between short period for the opportunity to atomize, evaporate and mix with air to take place. From spray characteristics, spray spread characteristics shows improvement of all tri-fuel emulsions as compared to diesel by 38.75% overall average enhancement. Average combustion characteristics result offered a positive outcome when the engine was running with no load. The heat release rate and in-cylinder pressure of tri-fuel emulsion during the ignition delay period exceed diesel. The peak of heat release rate and in-cylinder pressure of tri-fuel emulsion were improved compared to diesel.